Kutjamarcoot brevirostrum gen. et sp. nov., a new short-snouted, early Miocene bandicoot (Marsupialia: Peramelemorphia) from the Kutjamarpu Local Fauna (Wipajiri Formation) in South Australia. Issue 2 (2nd April 2016) - Chamberlain, P.M.; Travouillon, K.J.; Archer, M.; Hand, S.J.
Abstract : Chamberlain, P.M., Travouillon, K.J., Archer, M. & Hand, S.J., November 2015. Kutjamarcoot brevirostrum gen. et sp. nov., a new short-snouted, early Miocene bandicoot (Marsupialia: Peramelemorphia) from the Kutjamarpu Local Fauna (Wipajiri Formation) in South Australia. Alcheringa 40, XX–XX. ISSN 0311-5518. A new bandicoot species, Kutjamarcoot brevirostrum gen. et sp. nov. (Peramelemorphia), is described here from the Leaf Locality, Kutjamarpu Local Fauna (LF), Wipajiri Formation (South Australia). The age of the fossil deposit is interpreted as early Miocene on the basis of biocorrelation between multiple species in the Kutjamarpu LF and local faunas from the Riversleigh World Heritage Area (WHA). Kutjamarcoot brevirostrum is represented by isolated teeth and three partial dentaries and appears to have been short-snouted with an estimated mass of 920 g. Phylogenetic analyses place K. brevirostrum in a clade with extant Australian bandicoots and the extinct Madju, but potentially exclude the extant New Guinean bandicoots. Morphometric analysis infers close similarity between K. brevirostrum and species of Galadi in both size and rostral length. They, thus, potentially occupied compatible ecological niches with competitive exclusion perhaps explaining geographical segregation between these broadly coeval lineages. Philippa M. Chamberlain [ philippa.chamberlain@uq.net.au ], School of Earth Sciences, University of Queensland, St Lucia, Queensland 4072, Australia; Kenny J. Travouillon [ kenny.travouillon@museum.wa.gov.au ; kennytravouillon@hotmail.com ], Western Australian Museum, Locked Bag 49, Welshpool DC, WA, 6986, and School of Earth Sciences, University of Queensland, St Lucia, Queensland, 4072, Australia; Michael Archer [ m.archer@unsw.edu.au ] and Suzanne J. Hand [ s.hand@unsw.edu.au ], School of Biological, Earth and Environmental Sciences, University of New South Wales, New South Wales, 2052, Australia.